‘They Say HIV is a Punishment from God or from Ancestors’: Cross-Cultural Adaptation and Psychometric Assessment of an HIV Stigma Scale for South African Adolescents Living with HIV (ALHIV-SS) - Pantelic, M; Boyes, M; Cluver, L; Thabeng, M (Springer Verlag, 2016)
Sub-Saharan Africa is home to 90 % of the world’s adolescents living with HIV (ALHIV). HIV-stigma and the resultant fear of being identified as HIV-positive can compromise the survival of these youth by undermining anti-retroviral treatment initiation and adherence. To date, no HIV-stigma measures have been validated for use with ALHIV in Sub-Saharan Africa. This paper reports on a two-stage study in the Eastern Cape, South Africa. Firstly, we conducted a cross-cultural adaptation of an HIV stigma scale, previously used with US ALHIV. One-on-one semi-structured cognitive interviews were conducted with 9 urban and rural ALHIV. Three main themes emerged: 1) participants spoke about experiences of HIV stigma specific to a Southern African context, such as anticipating stigma from community members due to ‘punishment from God or ancestors’; 2) participants’ responses uncovered discrepancies between what the items intended to capture and how they understood them and 3) participants’ interpretation of wording uncovered redundant items. Items were revised or removed in consultation with participants. Secondly, we psychometrically assessed and validated this adapted ALHIV stigma scale (ALHIV-SS). We used total population sampling in 53 public healthcare facilities with community tracing. 721 ALHIV who were fully aware of their status were identified and interviewed for the psychometric assessment. Confirmatory factor analysis confirmed a 3-factor structure of enacted, anticipated and internalized stigma. The removal of 3 items resulted in a significant improvement in model fit (Chi2(df) = 189.83 (33), p < .001) and the restricted model fitted the data well (RMSEA = .017; CFI/TLI = .985/.980; SRMR = .032). Standardized factor loadings of indicators onto the latent variable were acceptable for all three measures (.41–.96). Concurrent criterion validity confirmed hypothesized relationships. Enacted stigma was associated with higher AIDS symptomatology (r = .146, p < .01) and depression (r = .092, p < .01). Internalized stigma was correlated with higher depression (r = .340, p < .01), higher AIDS symptomatology (r = .228, p < .01) and low social support (r = −.265, p < .01). Anticipated stigma was associated with higher depression (r = .203, p < .01) and lower social support (r = −.142, p < .01). The resulting ALHIV-SS has 10 items capturing all three HIV stigma mechanisms experienced by ALHIV. ALHIV-SS will be valuable for evaluating rates and types of stigma, as well as effectiveness of stigma-reduction interventions among ALHIV in Southern Africa.